Uji cemaran bakteri Coliform pada daging ayam broiler menggunakan metode MPN Coliform di UPT Laboratorium Kesehatan Hewan Dinas Peternakan Provinsi Jawa Timur di Tuban - Aditiya, Deby Putri (Maliki Interdisciplinary Journal, 2024)
Food safety is the main demand from consumers who must ensure that it is free from pathogenic bacterial contamination and is safe for consumption. One of the pathogenic bacteria found as a contaminant in broiler chicken meat is Coliform bacteria. This research aims to determine the results of the MPN Coliform test and its conformity with the maximum limit for microbial contamination according to SNI 7388 of 2009 on 4 samples of broiler chicken meat sold at the Montong market in Tuban district using a quantitative test, namely the Most Probable Number (MPN). The MPN method is a method for estimating and determining the amount of Coliform bacterial contamination found in broiler chicken meat samples in accordance with SNI 2897: 2008 guidelines regarding methods for testing microbial contamination in meat, eggs and milk and their processed products. The results obtained from this research were based on the MPN Coliform confirmation test, there was one sample with code A4 which exceeded the maximum limit for microbial contamination with a value of >1100 colonies/gram according to SNI 7388 of 2009.